Cytological intracellular glycogen evaluation using PAS and PAS-D stains to correlate plasma glucose in diabetics - S Shamala Ravikumar; T R Menaka; G Vasupradha; K Dhivya; J Dinakaran; V Saranya (Wolters Kluwer Medknow Publications, 2019)
Background: Oral cytology studies have claimed that cytoplasmic Periodic Acid Schiff (PAS) positivity in type-2 diabetics is due to glycogen content. But, it can also be due to mucin and glycoconjugates. Aim: 1. To confirm that cytoplasmic PAS positivity in type-2 diabetics is due to glycogen using diastase. 2. To know the effect of diabetes by determining the number of glycogen-containing cells in the smear. 3. To assess the impact of duration of diabetes based on PAS staining of cells. 4. To correlate between random blood glucose level and the number of PAS-positive cells. Materials and Methods: Study population comprised 45 individuals with 30 type-2 diabetics as case group (Group I < 5 years duration; Group II > 5 years duration) and 15 healthy volunteers (age and gender-matched) as control. For all subjects, random blood glucose was estimated and two cytosmears were obtained. The smears were stained with PAS and PAS-diastase stains (PAS-D). Staining intensity was documented as score 1 (mild-to-moderate) and score 2 (moderate-to-intense) and data obtained were statistically analyzed in SPSS version 16.0. Results: Mann-Whitney U test revealed that in diabetics cytoplasmic PAS positivity is because of glycogen (P < 0.05). There is an increase in the number of glycogen-containing cells (P < 0.05) in diabetics. The duration of diabetes had less impact on intracellular glycogen accumulation (P > 0.05). Spearman's correlation test revealed no significant correlation (P > 0.05) between random blood glucose and a number of PAS-positive cells. Conclusion: PAS positivity is because of intracellular glycogen accumulation in type-2 diabetics. It can convey the glycaemic status of an individual in the recent past, thus a beneficial role in screening and therapeutic monitoring.